Determining the taxol contents of yew tree populations in western Black Sea and Marmara regions and analyzing some forest stand characteristics - Tandogan, Mesut; Özel, Halil Barış; Gozet, Fatma Tuba; Sevik, Hakan (BioResources, 2023)
Yew tree (Taxus baccata L.) is mainly populated in Türkiye, Europe, and Caucasia regions. It has natural anticancer compounds and is a source of raw materials used in modern medicine. The present study aimed to examine the taxol contents of yew trees naturally grown in Marmara and Western Black Sea regions by subjecting needle samples taken from 17 yew populations to extraction and liquid chromatography tandem mass / mass spectrometer system (LC-MS/MS) analysis. It was also examined whether a relationship exists between some stand characteristics and taxoid contents of the needles. From these analyses, the highest taxol contents were found in Bartın-Gölderesi, Yığılca-Kurtkayası, İnebolu-Karagöl, and Yenice-Kızılkaya populations. The statistical analyses showed that there were significant relationships between compound contents and slope, humus content, total nitrogen content (%), and potassium (K). It is recommended to use these derivatives obtained from natural forests in sapling nursing and tissue culture studies, to produce pharmaceutical materials from leaves and protect and improve the current gene sources.
Keywords: Taxus Baccata L; taxol; Taxol; Lc-Ms; Ms; lc-ms/ms; forest stand; Forest Stand; TP248.13-248.65; taxus baccata l.; Biotechnology